Quantitative real-time PCR detection and analysis of a lumpy skin disease outbreak in Inner Mongolia Autonomous Region, China - Li, Lin; Qi, Chuanxiang; Li, Jinming; Nan, Wenlong; Wang, Ying; Chang, Xing; Chi, Tianying; Gong, Mingxia; Ha, Da; De, Jide; Ma, Lifeng; Wu, Xiaodong (Frontiers in Veterinary Science, 2022)
Lumpy skin disease (LSD) is a severe disease of bovine characterized by nodules on the skin, mucous membranes and profuse nasal discharge which caused severe economic losses. In Oct, 2020, an LSD outbreak case was found in Inner Mongolia Autonomous Region, China. 1206 cattle were sold from the same imported animal quarantine field to 36 farms after the quarantine period finished, and over 30 farmers reported symptoms such as skin scabs were found in newly arrived cattle shortly after that. Large-scale LSD outbreak investigation launched after laboratory diagnosis confirmed LSD. The clinical samples of 1206 cattle from 36 farms, including 1206 whole blood, 1206 oral and nose swabs and 355 scabs, were collected for Quantitative Real-time PCR (qPCR) test. The result showed that 51 whole blood samples (4.23%), 580 swab samples (48.09%) and 350 skin scabs (98.59%) were LSDV positive, 33 of 36 farms were affected. This study aims to provide a basis for LSD epidemiological traceability, movement control and measures for prevention and control.